Design of a high-speed high-accuracy 2048-point FFT using single-precision floating-point adaptive cordic on FPGA - TRUONG, Nhu-Quynh; HOANG, Trong-Thuc; PHAM, Cong-Kha; LE, Duc-Hung (Vietnam Journal of Science and Technology, 2018)
In this paper, hardware design of a Fast Fourier Transform (FFT) core using Single-precision Floating-point Adaptive CORDIC is implemented on Altera Stratix IV FPGA. With FFT implementation, CORDIC is utilized for reducing the speed drawback of complex multiplication and the adaptive algorithm is proposed to decrease the iterations of conventional CORDIC. The experimental results of Adaptive CORDIC and 2048-point Radix-2 Multi-path Delay Commutator FFT designs are built and verified based on three kinds of Look-up Table that cost 16, 8 and 4 constant angles. As experimental results, there is a resource equivalence while it has a trade-off between speed performance and accuracy. In comparison, an adaptive CORDIC core based on Look-up Table of 16 constant angles, and 2048-point Radix-2 Multi-path Delay Commutator Fast Fourier Transform based on Adaptive CORDIC using Look-up Table of 16 constant angles are well responding to resource optimization, high-speed performance and high-accuracy of computations.